2007
DOI: 10.1080/09593332808618806
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and Kinetics of Metal Biosorption by Sludge from a Biological Nutrient Removal System

Abstract: This study investigated the biosorption kinetics and equilibrium of cadmium, nickel and zinc by activated sludge from a biological nutrient removal (BNR) process. A series of batch experiments with different initial metal concentrations were conducted to determine the metal removal in BNR sludge. The harvested sludges were from a continuous-flow anaerobic-anoxic-oxic (A2O) system operated under a 10 days of sludge retention time. Batch tests were specially designed to isolate the precipitation effects of metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
1
4
0
2
Order By: Relevance
“…Removal was observed to be complete within 5 min, and metals were not observed to go back into solution during the 120 min contact period. Rapid (3-10 min) metal uptake by AS has been described previously (Chang et al, 2007;Cheng et al, 1975), and Yuncu et al (2006) reported that uptake of high concentrations of Cd, Cu, Ni and Zn was almost 85%…”
Section: Metal Removal Studiessupporting
confidence: 60%
See 1 more Smart Citation
“…Removal was observed to be complete within 5 min, and metals were not observed to go back into solution during the 120 min contact period. Rapid (3-10 min) metal uptake by AS has been described previously (Chang et al, 2007;Cheng et al, 1975), and Yuncu et al (2006) reported that uptake of high concentrations of Cd, Cu, Ni and Zn was almost 85%…”
Section: Metal Removal Studiessupporting
confidence: 60%
“…In practice, the removal of metals from WW during treatment using the AS process is primarily controlled by entrapment and settlement of particulate non-settleable metal-containing solids (Brown and Lester, 1979;Santos et al, 2010), and suspended solids removal is therefore of utmost importance (Goldstone et al, 1990a). Particularly at high influent concentrations, it would be expected that significant fractions of metals would be removed from solution by precipitation (Chang et al, 2007;Cheng et al, 1975), in addition to removal via other means.…”
Section: Metal Removal Studiesmentioning
confidence: 99%
“…Ion exchange (Ca(II), Mg(II), H + ) is also involved [19,45,48,49] as well as precipitation [50]. In this study, the evolutions of some of these mechanisms were investigated with regards to the metal species and the specific energy previously applied to the sludge.…”
Section: Investigation On the Mechanisms Of Metal Biosorptionmentioning
confidence: 99%
“…This increase in pH indicates that neutralization of AMD occurs when it is mixed with activated sludge. Metals are removed from solution in WWTPs via several mechanisms, including adsorption onto activated sludge biomass and EPS (Battistoni et al 1993;Brown and Lester 1979;Cheng et al 1975;Guibaud et al 2003), precipitation and entrapment by activated sludge flocs (Chang et al 2007;Pagnanelli et al 2009;Sterritt et al 1981), and chelation onto organic compounds in wastewater (Arican and Yetis 2003;Kunz and Jardim 2000;Nicolau et al 1999;Sterritt and Lester 1984). The pH is an important factor in all of Table 6 Results of OUR inhibition tests performed with simulated Avoca AMD and activated sludge samples from Reactor A (Control), and Reactors B, C, and D, which were loaded with 5, 10, and 25% AMD as a fraction of total influent volume during the acclimatization study these metal removal mechanisms.…”
Section: Acute Toxicity Testsmentioning
confidence: 99%